Isolation and Molecular Identification of Lactic Acid Bacteria Using 16s rRNA Genes from Fermented Teff (Eragrostis tef (Zucc.)) Dough. (5th August 2018) - Tilahun, Belay; Tesfaye, Anteneh; Muleta, Diriba; Bahiru, Andualem; Terefework, Zewdu; Wessel, Gary
Abstract : Injera is soft fermented baked product, which is commonly prepared from teff ( Eragrostis tef (Zucc . )) flour and believed to be consumed on daily basis by two-thirds of Ethiopians. As it is a product of naturally fermented dough, the course of fermentation is done by consortia of microorganisms. The study was aimed at isolating and identifying some dominant bacteria from fermenting teff (Eragrostis tef) dough. A total of 97 dough samples were collected from households, microenterprises, and hotels with different fermentation stage from Addis Ababa. The bacterial isolates obtained from the fermenting teff dough samples were selected on the basis of their acid production potentials. A total of 24 purified bacterial isolates were found to be Gram-positive (they are coccus and rod under microscope) and were good acid producers. Genomic DNA of bacterial isolates were extracted using Invisorb® Spin DNA Extraction kit. 16S rRNA of bacterial isolates were amplified using the bacteria universal primers (rD1 and fD1). The amplified product was sequenced at Genewiz, USA. Sequence analysis and comparison with the resources at the database were conducted to identify the isolated microbes into species and strain levels. The bacterial isolates were identified as Lactobacillus paracasei, Lactobacillus brevis, Enterococcus durans, Enterococcus hirae, Enterococcus avium, and Enterococcus faecium . All identified lactic acid bacteria were able to produce acid at 12 h time of incubation. This study has confirmed the presence of different bacterial species in the fermenting teff dough and also supports the involvement of various groups of bacterial species in the course of the fermentation.